Tuning the Electron Acceptor in Phthalocyanine‐Based Electron Donor–Acceptor Conjugates. Issue 52 (23rd November 2015) - Sekita, Michael; Jiménez, Ángel J.; Marcos, M. Luisa; Caballero, Esmeralda; Rodríguez‐Morgade, M. Salomé; Guldi, Dirk M.; Torres, Tomás
Abstract: Zinc phthalocyanines (ZnPc) have been attached to the peri ‐position of a perylenemonoimide (PMI) and a perylenemonoanhydride (PMA), affording electron donor–acceptor conjugates 1 and 2, respectively. In addition, a perylene‐monoimide‐monoanhydride (PMIMA) has been connected to a ZnPc through its imido position to yield the ZnPc‐PMIMA conjugate 10 . The three conjugates have been studied for photoinduced electron transfer. For ZnPc‐PMIMA 10, electron transfer occurs upon both ZnPc and PMIMA excitation, giving rise to a long‐lived (340 ps) charge‐separated state. For ZnPc‐PMI 1 and ZnPc‐PMA 2, stabilization of the radical ion pair states by using polar media is necessary. In THF, photoexcitation of either ZnPc or PMI/PMA produces charge‐separated states with lifetimes of 375 and 163 ps, respectively. Abstract : Long‐lived charge separation : Perylenemonoimides (PMI), perylenemonoanhydrides (PMA), and perylene‐monoimide‐monoanhydrides (PMIMA) are studied as the oxidizing counterpart of phthalocyanines in electron donor–acceptor hybrids. The three systems show different degrees of orbital partitioning and generate long‐lived charge‐separation states upon photoexcitation.